Mycobacterium celatum encephalitis in an immunocompromised host mimicking autoimmune striatal encephalitis: the first case report - Thanapoom Taweephol; Thanakit Pongpitakmetha; Prakit Anukoolwittaya; Chayoot Marukatat; Wanakorn Rattanawong; Pasin Hemachudha; Jakapat Vanichanan; Suwatchareeporn Rotcheewaphan; Abhinbhen W. Saraya (My University, 2025)
Encephalitis is rarely caused by nontuberculous mycobacteria (NTM), which is generally not considered a highly virulent pathogen. However, NTM encephalitis in immunocompromised hosts occurs with varied clinical presentations, posing a diagnostic challenge in clinical practice. This study aims to describe an atypical case of NTM encephalitis caused by Mycobacterium celatum, which has not previously been reported to infect the central nervous system of immunocompromised hosts, mimicking autoimmune striatal encephalitis (ASE). A 35-year-old immunosuppressed woman presented with prolonged fever for 4 months and rapidly progressive cognitive decline for 3 months. Neurological examination showed impaired cognition and parkinsonism. Laboratory testing was unremarkable. Her brain imaging on T2-weighted fluid-attenuated inversion recovery (T2/FLAIR) exhibited lesions involving basal ganglia and subcortical white matter in both hemispheres, mimicking ASE. Cerebrospinal fluid (CSF) analysis revealed mild pleocytosis with normal glucose and protein levels. CSF comprehensive microbiological studies and autoimmune panels were negative. ASE was suspected, and immunotherapies were given. Despite immunotherapies, her condition worsened with seizures, warranting a stereotactic brain biopsy to achieve a definite diagnosis. Her brain tissue pathology result was non-specific. However, we identified M. celatum from her brain tissue. Thus, the final diagnosis was M. celatum encephalitis. Therefore, we discontinued immunotherapies and started anti-NTM treatment, including isoniazid, rifampicin, ethambutol, and levofloxacin. After completing a 16-month treatment course, her clinical condition was stable, afebrile, and seizure-free. We proposed that NTM invades the central nervous system and also triggers immune dysregulation, developing features resembling ASE. In case of suspicious autoimmune encephalitis with poor response to immunotherapies, a tissue biopsy should be performed to exclude chronic infection.
Keywords: Medical microbiology; Parasitology; Autoimmune encephalitis; Mycobacterium research and diagnosis